Increasing Students' Interest in Learning through the "Make A Match Type" Learning Model in KKPI Subjects - Akmal, Munzir; Nurhasanah, Nurhasanah (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2016)
This technique can be used in all subjects and for all ages of students. In the implementation of this make and match learning model a teacher must prepare a card containing the problem or problem and prepare the answer card then the students look for the pair of cards. By using this learning model, it is expected the interest or passion of learning and cooperation among students will be better. In this class action research (PTK) aims: (1) To improve students' ability in operating Microsoft Excel software. (2) To increase students 'learning interest in operating Microsoft Excel (3) To know the effectiveness of the use of model make-match type learning in improving students' interest in operating Microsoft Excel software. Implementation of this research is done through Classroom Action Research (PTK) in class X Administration Office 1 SMK Negeri 1 Batanghari. Based on the research findings, the following suggestions are proposed: (1) A teacher must be able to choose the right learning model, so that the learning objectives can be achieved as expected. (2) In order for teachers to try to apply the Make a Match learning model as an alternative in implementing learning, so that learning is fun and not boring. (3) In order for good cooperation between teachers, students and schools can always be improved in order to support success in the learning process at school.